PENERAPAN EKONOMI SIRKULAR MELALUI PENYULUHAN BRAND DAN PENGEMASAN PRODUK JAMUR PADA POKMAS PELITA BERKARYA DI DESA PENYANGGA TAMAN NASIONAL MERU BETIRI - Lenny Luthfiyah Lenny Luthfiyah Lenny Luthfiyah; Rizky Yanuarti; Laily Mutmainnah (Universitas Muhammadiyah Sidenreng Rappang, 2025)
Abstract: This community service program was carried out to strengthen the capacity of the Pokmas Pelita Berkarya group, which consists of former illegal loggers in the buffer village of Meru Betiri National Park, through the application of circular economy principles in mushroom cultivation. The main problem faced by the group was the low added value of their mushroom products due to limited marketing, lack of product identity (branding), and non-standard packaging that did not meet the requirements of the National Food Agency. To address this issue, participatory extension activities were conducted focusing on brand development, packaging standards, and digital payment adoption with QRIS. The activities included need assessment, interactive presentations, group discussions, and simple practice in designing labels and packaging. The results showed a significant increase in participants’ understanding of branding as not only a visual identity but also a strategic tool for building product reputation and consumer trust. Moreover, they recognized the importance of packaging that ensures product quality, safety, and competitiveness in modern markets. The introduction of QRIS also encouraged participants to adopt digital transactions, enhancing professionalism and market reach. Overall, the program successfully improved the knowledge and skills of the community, created social-ecological transformation narratives, and strengthened the sustainability of mushroom businesses aligned with circular economy practices. Abstract: Program pengabdian masyarakat ini dilaksanakan untuk memperkuat kapasitas Kelompok Masyarakat (Pokmas Pelita Berkarya) yang terdiri atas mantan pelaku illegal logging di desa penyangga Taman Nasional Meru Betiri melalui penerapan prinsip ekonomi sirkular pada usaha budidaya jamur. Permasalahan utama yang dihadapi mitra adalah rendahnya nilai tambah produk akibat pemasaran terbatas, belum adanya identitas merek (branding), serta kemasan yang belum memenuhi standar Badan Pangan Nasional. Untuk mengatasi hal tersebut dilakukan kegiatan penyuluhan partisipatif yang berfokus pada pengembangan brand, standar pengemasan, serta adopsi pembayaran digital dengan QRIS. Kegiatan meliputi identifikasi kebutuhan, presentasi interaktif, diskusi kelompok, dan praktik sederhana dalam mendesain label dan kemasan. Hasil kegiatan menunjukkan peningkatan signifikan pemahaman peserta bahwa brand bukan hanya logo, melainkan strategi membangun reputasi dan kepercayaan konsumen. Peserta juga menyadari pentingnya pengemasan sesuai standar untuk menjamin mutu, keamanan, dan daya saing produk di pasar modern. Selain itu, pengenalan QRIS mendorong keterbukaan terhadap transaksi digital sehingga meningkatkan profesionalisme usaha. Secara keseluruhan, program ini berhasil meningkatkan pengetahuan dan keterampilan masyarakat, memperkuat narasi transformasi sosial-ekologi, serta mendukung keberlanjutan usaha jamur sesuai prinsip ekonomi sirkular.